The Study Of Educative Value In Wawi Dadi Rite - Veni, Vinsensia Nona (CV. ITTC INDONESIA, 2022)
This research was aimed to find out and explore the educational values contained in the wawi dadi ceremony. This research was conducted in Hale village. This study uses a qualitative method. Sources of data can be obtained through interviews, documentation. The results of the study describe the educational values contained in the wawi dadi ceremony including (1) the value of loyalty, (2) the value of responsibility, and, (3) the value of harmony. Based on the results of the study, the conclusion is that some of the educational values contained in the wawi dadi ceremony are emphasized to young people so that they want to open up and want to learn to understand and explore the noble values of culture such as the wawi dadi rite. With this very rapid technological advancement, it can be supported by education, good and correct coaching so that easy people do not fall into the trap of the progress of the modern world.